2018
DOI: 10.1016/j.scr.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

NEK1 loss-of-function mutation induces DNA damage accumulation in ALS patient-derived motoneurons

Abstract: Mutations in genes coding for proteins involved in DNA damage response (DDR) and repair, such as C9orf72 and FUS (Fused in Sarcoma), are associated with neurodegenerative diseases and lead to amyotrophic lateral sclerosis (ALS). Heterozygous loss-of-function mutations in NEK1 (NIMA-related kinase 1) have also been recently found to cause ALS. NEK1 codes for a multifunctional protein, crucially involved in mitotic checkpoint control and DDR. To resolve pathological alterations associated with NEK1 mutation, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 38 publications
0
80
0
Order By: Relevance
“…Additionally, it is worth mentioning that Nguyen et al [45] conducted a cohort study and characterized the genetic viability of NEK1 in ALS and frontotemporal dementia ALS (FTD-ALS) patients. Finally, it was demonstrated that the DNA damage accumulation was activated by variants of NEK1 in motoneurons derived from patients [46]. Other ALS-genes were also related to DDR mechanisms, such as FUS1 and C9orf72, which supports the idea that NEK1 plays a role in ALS, since it was also demonstrated to be involved in the DDR.…”
Section: Nek1mentioning
confidence: 56%
“…Additionally, it is worth mentioning that Nguyen et al [45] conducted a cohort study and characterized the genetic viability of NEK1 in ALS and frontotemporal dementia ALS (FTD-ALS) patients. Finally, it was demonstrated that the DNA damage accumulation was activated by variants of NEK1 in motoneurons derived from patients [46]. Other ALS-genes were also related to DDR mechanisms, such as FUS1 and C9orf72, which supports the idea that NEK1 plays a role in ALS, since it was also demonstrated to be involved in the DDR.…”
Section: Nek1mentioning
confidence: 56%
“…Loss of function due to mislocalization results in a loss of VPS4B repression leading to an increased interaction with the ALS-linked protein Charged Multivesicular Body Protein 2B (CHMP2B) thereby disrupting dendritic recycling-endosome trafficking and reducing ALS-linked ERB-B2 Receptor Tyrosine Kinase 4 (ERBB4) surface expression [191][192][193]. Another nuclear role for TDP-43 is in its response to genomic double stranded breaks (DSBs) which accumulate in ALS patients [163,[194][195][196][197][198][199][200]. Mislocalization of TDP-43 through an ALS-causing mutation impair the nuclear localization of DSB-repair proteins and result in the accumulation of DNA damage promoting cell death [163,194,201,202].…”
Section: The Contribution Of Tdp-43 Mislocalization To Cellular Toxicmentioning
confidence: 99%
“…Patients and controls gave their written informed consent prior to skin biopsy. The generation and expansion of iPSC lines from healthy control and familiar ALS patients with defined mutations in the FUS or TDP43 gene and HREs in C9ORF72 (table 1) was recently described (5,11,17,(53)(54)(55). Isogenic C9-KO and C9-GC lines from parental C9 (table 1) were generated by CRISPR-Cas9n-mediated gene-editing and fully characterized in the Sterneckert laboratory (32).…”
Section: Mfcsmentioning
confidence: 99%